Outcomes Prediction Using qSOFA, SpO2 / FiO2 and Procalcitonin of Pneumonia Sepsis Patients In Lung Ward at Dr. M.Djamil Padang Hospital - Irawan, Eka; Medison, Irvan; Khairsyaf, Oea; Anggraini, Fenty (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Sepsis is a systemic inflammatory response to severe infections, sepsis is a major cause of morbidity and mortality. This study aims to determine the outcome prediction using qSOFA, SpO2/FiO2 Rasio and Procalcitonin in sepsis pneumonia patients in Lung ward of Dr. M DJamil Padang Hospital. Methods: Cohort study design with correlative analytics for 43 pneumonia sepsis patiens in Lung ward at Dr. M. Djamil Padang Hospital from September 2019 until to Februari 2020. Samples were taken by consecutive sampling method. Results: There were a significant relationship between qSOFA score with procalcitonin (p value = 0.006). There were no significant relationship between SpO2/FiO2 Rasio with procalcitonin (p value = 0.128). There were a significant relationship between qSOFA scores with patient outcomes (p value = 0.036), there were no significant relationship between procalcitonin with patient outcomes (p value = 0.205), and there were a significant relationship betweenSpO2/FiO2 Rasio with patient outcomes (p value = 0.019). Conclusion: qSOFA and SpO2 / FiO2 Rasio can predict the outcomes of patients with sepsis pneumonia